Improving welfare on 25 Holstein-Friesian farms in Hungary - Gudaj, Richard; Brydl, Endre; Komlósi, István (Animal Welfare, Etológia és Tartástechnológia (AWETH), 2012)
Welfare of 11 422 dairy cows, 2153 dry cows, 5175 heifers, 4934 calves > 70 days, and 2170 calves < 70 days was evaluated on 25 Hungarian Holstein-Friesian farms in 2010 and 2011. Advices were given to farmers regarding the weakest areas on the farms regarding welfare measures and welfare in 2010 and were checked again in 2011. The Shapiro-Wilk test was used to check the normality of animal welfare measures. Multiple factor analysis of variance (for normally distributed data) and Mann-Whitney test (for not normally distributed data) was performed to observe differences in animal welfare measures between 2010 and 2011. A Spearman Rank Correlation test was run to find correlations between animal welfare measures and environmental factors. A Chi-square test for relatedness or independence was used to evaluate the differences in animal welfare distributions on farms between 2010 and 2011. Advices given to farmers significantly affected improvement in cleanliness of all groups of cattle and improvement of body conditions of thin younger calves, fat heifers and fat milking cows. There were less obviously ill heifers reported and less neck rail injuries among heifers, dry and milking cows. Decrease in welfare was observed in older calves with dirtier hindlimbs, higher number of thin heifers and milking cows. Higher number of older calves with diarrhoea and more dry and milking cows being obviously ill were estimated. After the advice, more lameness and not normal behaviours were found in milking cows. There was also higher number of hock injuries discovered among older calves, heifers, dry and milking cows. Finally, more neck rail injuries among older calves with more non-hock injuries in heifers and dry cows were observed. Totally, 18 improved and 14 worst measures were discovered after providing farmers with dairy welfare solutions. Results found in the study confirm that farmers choose between improved cleanliness with better body conditions and more ill cattle with injuries. It can be explain either because those aims were the easiest to achieve or this is how welfare is perceived by farmers.